Hak asuh anak pasca perceraian dalam perspektif hukum Islam dan hukum positif di Indonesia - Rahman, Babur; Paripati Qomaria , Nanik (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
This article discusses child custody rights after divorce from the perspective of Islamic law and civil law. The provisions regarding child custody are contained in Law no. 1 of 1974, stated in article 54 paragraph (2)